Age-related sarcopaenia of the posterior pharynx in a cadaveric population - Fitchat, Nicolas Allyn (My University, 2021)
Sarcopaenia is the loss of muscle associated with ageing. Dysphagia is a disruption in the correct functionality of the pharyngeal muscles with significant implications. Objective To investigate the degree of Sarcopaenia in the posterior pharynx in a cadaveric population and its correlation with age at the time of death and sex as a possible contributing factor leading to the development of dysphagia. Methods Retrospective review of data collected from 109 cadavers was analysed, 52 males and 57 females. A total of 86 cadavers met the inclusion criteria, 42 males and 44 females. Mean measurements at four aspects of the posterior laryngopharynx at the level of the inferior pharyngeal constrictor were analysed and correlated with age. These means were further compared in cadavers 65 years and younger, and those older than 65 years. This mean was also compared between the two sexes. A paired student’s T test and a one sample T test were used to test for significance. Results A positive correlation was found between age and the mean of the muscle thicknesses of the posterior laryngopharynx. A significant difference was found between the groups of cadavers divided between those 65 years and younger and older than 65 years. No significant difference was found between the muscle thickness of the posterior laryngopharynx and sex of the cadaver. Conclusion There was a positive correlation between age and the mean muscle thickness of the posterior laryngopharynx. Showing that the muscle is thicker in older cadavers. Furthermore, the muscle thickness is significantly thicker in those more than 65 years than those 65 years and less. It has been shown by multiple previous studies that have shown that constriction of the pharynx appears to decline with age. Other studies have however shown that the force generated during swallowing in the pharynx does appear to increase with age. This has been postulated to be a compensatory response to the decrease in compliance of the cricopharyngeus muscle, as the upper oesophageal constrictor (UES), due to a replacement of normal muscle and connective by fibroadipose tissue. As a part of sarcopaenia where there is a complex interplay between atrophy and hypertrophy, hypertrophy appears to be the most prominent feature in the posterior laryngopharynx of the elderly as is demonstrated by a thicker muscle layer in our older individuals. This hypertrophy may be a compensatory effect due to the loss of muscle fibres due to atrophy as has been previously explored by other authors. There appears to be no statistically significant difference in this muscle thickness between sexes. This hypertrophy may be a compensatory effect due to the loss of muscle fibres due to atrophy as has been previously explored by other authors. This may also be a possible reason to explain the increase in the force of contraction during swallowing to overcome the resistance that a food bolus requires to overcome the resistance within the UES, which has been shown to be less compliant in aged individuals, in order to pass into the proximal oesophagus.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine (Internal Medicine) to the Faculty of Health Sciences, School of Internal Medicine, University of the Witwatersrand, Johannesburg, 2021